State and Challenges for the Development of Cooperation in Science and Technology between Russia and China - I. V. Danilin (Модернизация, инновация, развитие, 2020)
Purpose: the main purpose of this article is to analyze the state and prospects of science and technology (S&T) cooperation between the Russian Federation and the PRC in the context of the global S&T cooperation trends.Methods: research is based on a combination of desk and field methods. The article is based on the data from official documents of the Russian Federation, state companies, institutions for development, and other structures, as well as media sources. A series of non-focused expert interviews with representatives of the innovation and expert community, linked to Russia-China S&T cooperation, was also conducted.Results: the main trends and directions of the S&T cooperation between Russia and China in 2000–2020s have been identified, including: large projects in traditional medium- and high-tech industries; horizontal academic cooperation; bilateral activities in developing innovation infrastructure (science parks, investment funds, etc.); tech activities of big corporations – with special focus on Huawei. Several factors, limiting the potential of bilateral S&T cooperation, were identified. Among the most important are: differences in the structure of real (not declarative) S&T priorities; weak complementarity of both economies and unwillingness to form harmonized trade and investment regimes (also because of the different size of Russian and Chinese economies); the techno-nationalist ideology of state policies of both nations; mismatching areas of scientific leadership that impedes synergy in academic research. The fragmentation and insufficient financial support of the Russian S&T and innovation sectors are noted as separate factors.Conclusions and Relevance: despite high mutual interest in intensification of Russia-China dialogue is declared, there are clear limits for bilateral S&T cooperation. Existing restrictions predetermines the preservation of a relatively small scale of S&T cooperation for the foreseeable future, with P2P interactions of groups of actors at its core. However, some of these interactions may be large-scale and long-term, as is the case of Huawei. One of the ways to change this dynamic (not saying about urgent need to optimize economic situation in Russia) is to develop a comprehensive strategy of cooperation with China – with subsequent focus on a small group of most important initiatives and creating favorable conditions for interaction of private and academic actors.